2019
DOI: 10.17557/tjfc.562637
|View full text |Cite
|
Sign up to set email alerts
|

The Parametric and Non-Parametric Stability Analyses for Interpreting Genotype by Environment Interaction of Some Soybean Genotypes

Abstract: Seed yields of 15 soybean genotypes were evaluated in three locations i.e. Bursa, Samsun and Konya under main crop conditions through summer seasons from 2014 to 2016. The used design was a randomized complete block design with four replications. This research is aimed to estimate the stability parameters of seed yield of 15 soybean genotypes by used different stability analysis methods over nine environmental conditions and to study interrelationship among these stability methods. Genotypes, environments and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 34 publications
0
21
0
1
Order By: Relevance
“…Efek GxE telah banyak dipelajari secara luas oleh para pemulia tanaman dalam menyeleksi genotipe yang stabil dan berdaya hasil tinggi. Berbagai metode telah diusulkan untuk dapat digunakan sebagai indeks seleksi bersama dengan hasil rata-rata peringkat stabilitas genotipe (Farshadfar et al, 2012;Abate et al, 2015;Khalili dan Pour-aboughadareh, 2016;Goksoy et al, 2019;Vaezi et al, 2019). Dalam penelitian ini, digunakan beberapa pengukuran stabilitas parametrik dan non-parametrik, serta model GGE biplot untuk mengidentifikasi genotipe ubi jalar yang stabil dan berdaya hasil tinggi.…”
Section: Pengukuran Stabilitas Dengan Model Parametrik Dan Nonparametrikunclassified
“…Efek GxE telah banyak dipelajari secara luas oleh para pemulia tanaman dalam menyeleksi genotipe yang stabil dan berdaya hasil tinggi. Berbagai metode telah diusulkan untuk dapat digunakan sebagai indeks seleksi bersama dengan hasil rata-rata peringkat stabilitas genotipe (Farshadfar et al, 2012;Abate et al, 2015;Khalili dan Pour-aboughadareh, 2016;Goksoy et al, 2019;Vaezi et al, 2019). Dalam penelitian ini, digunakan beberapa pengukuran stabilitas parametrik dan non-parametrik, serta model GGE biplot untuk mengidentifikasi genotipe ubi jalar yang stabil dan berdaya hasil tinggi.…”
Section: Pengukuran Stabilitas Dengan Model Parametrik Dan Nonparametrikunclassified
“…According to Ahmadi et al 18 , selection of stable genotypes with one stability measurement was considered less effective and accurate. The same thing was also expressed by several researchers who used various stability measurements to select stable and high-yielding genotypes, including barley 20 , sweet potatoes 7,9 , and soybeans 24 . Each stability measurement generally selects a different hybrid as the most stable.…”
Section: Discussionmentioning
confidence: 80%
“…Besides parametric and non-parametric statistics, biplot graphs improved the success in identifying the stability parameters suitable for selections in safflower breeding programs. Similarly, Vaezi et al (2019) in barley, Goksoy et al (2019) in soybean, Oyekunle et al (2016) in maize and Jamshidmoghaddam and Pourdad (2013) in safflower, indicated significant advantages of combined use of parametric and non-parametric stability statistics with GGE biplot approaches in identification of stable genotypes.…”
Section: Resultsmentioning
confidence: 99%